Maintaining ISO 9001:2015 in Higher Education Institutions in Cordillera Administrative Region, Philippines - Jessie B. Martinez (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study examines the level of agreement on the practices for maintaining the ISO 9001:2015 (QMS) of the Support Service Units in three higher education institutions in Cordillera Administrative Region (CAR), Philippines. Documenting practices and strategies aims to enrich scientific knowledge and potentially encourage non-ISO-certified HEIs in the region to pursue certification. Methodology: This study used quantitative and qualitative approaches, employing survey and descriptive research designs. A survey questionnaire gathered interval data on a 4-point scale to describe process owners' agreement on practices. Meanwhile, answers to open-ended questions were collected, categorized and analyzed using thematic analysis, providing solid explanations of practices in selected Philipine HEIs. Main Findings: The study revealed strong agreement in all indicators for maintaining the ISO 9001:2015 (QMS) certification in the three HEIs. This implies that respondents acknowledged these practices vital to maintaining the QMS certification status. Overall, maintaining the QMS status requires constant communication, comprehensive documentation, and regular reviews for continuous improvement on the processes and service delivery of the support service units. Novelty/Originality of this study: Research documenting the implementation of ISO QMS of the Support Service Units of the HEIs in CAR is limited. Thus, this study is relevant to document the practices, aligning with ISO quality management principles, QMS standards, PDCA cyle and elements for maintaining the ISO 9001:2015 QMS of the ISO-certified private and state university in the region. Finally, this study provides a basis for other HEIs as they undergo certification.